Features and factors of professional self-fulfillment of skilled people - Oleg M. Kokun (Social Welfare: Interdisciplinary Approach)
The objective tendencies of social development determine significantly increased attention to the problem of persons’ self-fulfillment. Lack of knowledge on this phenomenon dictates the need for its theoretical justification as well as for empirical studies. This paper presents the results of a research aimed at determination of features and factors of professional self-fulfillment of skilled people of different ages and professions.